Enduring inequality: Long-term trends and factors in participation in adult education and learning among older adults - Kalenda, Jan; Kočvarová, Ilona (Gerontology & geriatrics education, 2024)
Non-formal adult education and learning (NAE) is widely recognized as enhancing the quality of life and promoting active aging. Despite the empirically demonstrated benefits, older adults rank among one of the populations participating the least in NAE. Although several studies have highlighted the negative effect of aging on involvement in NAE, factors causing long-term changes in participation have not been explored directly. As a result, the significance of microsocial characteristics and their transformation over time has been overlooked. This article explores key microsocial factors leading to non/participation in NAE among adults aged 50 to 69 years along with changes in these factors for the 14-year period of 2006 to 2019. The research was conducted using the Czech Republic's Labor Force Survey dataset (N = 114,345). The results show that all microsocial factors play an essential role in determining participation in NAE, thus a strong relationship between the social origins (cumulative disadvantage) of older adults and their participation was confirmed. In addition, the impact of most factors has proved consistent over time, not strengthening since 2009. One exception was level of education, which showed a rapid increase in participation in NAE in the respondents who identified themselves as low-educated.
Keywords: Educational Status; stárnutí; kvalita života; Quality of Life; Employment; Aging; Social Participation; lidé; zaměstnanost; senioři; stupeň vzdělání; Humans; geriatrie; zapojení do společnosti; Geriatrics; Aged